The Effect of Cigarette Smoke Exposure on Blood Nicotine and Glutathione (GSH) Levels in Smokers and Non-Smokers - Ersalina Nidianti; Herlianti Anggun Puspita Ningrum; Silva Havadoh Shelagita; Ary Andini; Muhammad Afwan Romdloni (Window of Health : Jurnal Kesehatan, 2026)
Smoking remains a major global public health problem and contributes substantially to morbidity and mortality worldwide. According to the World Health Organization, tobacco use causes more than 8 million deaths annually, including approximately 1.3 million deaths among non-smokers exposed to secondhand smoke. Cigarette smoke contains nicotine and various oxidant compounds that promote free radical formation and oxidative stress, potentially disrupting the antioxidant defense system, including reduced glutathione (GSH), an important intracellular antioxidant. However, evidence simultaneously comparing nicotine exposure and GSH levels between smokers and non-smokers remains limited, particularly in the studied population. This study aimed to compare blood nicotine and GSH levels between smokers and non-smokers. An observational analytical study with a cross-sectional design was conducted among 34 respondents, comprising 17 smokers and 17 non-smokers. EDTA plasma samples were analyzed using UV–Vis spectrophotometry at 258 nm for nicotine and 412 nm for GSH. Differences between groups were analyzed using the Mann–Whitney U test. The mean nicotine level was higher in smokers than in non-smokers (19.18 vs. 5.51 µg/mL), whereas the mean GSH level was lower in smokers than in non-smokers (27.00 vs. 38.82 mg/dL). Significant differences were observed in both nicotine and GSH levels between the two groups (p < 0.001). These findings indicate that smoking is associated with higher nicotine levels and lower GSH levels, suggesting an imbalance in antioxidant defense consistent with increased oxidative stress among smokers.